2022
DOI: 10.7759/cureus.28452
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Sedative Efficacy of Dexmedetomidine and Midazolam in Pediatric Dental Practice: A Systematic Review and Meta-Analysis

Abstract: Children are particularly terrified of having dental treatment. They are physically resistant, frail, and unwilling to cooperate. This severe distress during the pre-operative phase could cause the dentist to have issues with behavior control. Additionally, it may make pediatric dental treatments less effective. In order to reduce anxiety and control behavior in children receiving dental care, sedation is a pharmacological management technique that supports the provision of effective and high-quality dental se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In addition, it comes in agreement with the previous meta-analyses that showed the beneficial effects of dexmedetomidine in different types of surgeries [35][36][37][38][39][40][49][50][51]. Moreover, a previous meta-analysis conducted by Liu et al [52] evaluating the efficacy and safety of dexmedetomidine in patients who had undergone transsphenoidal surgical resection of pituitary adenoma, including four randomized controlled trials with a total of 160 patients showed that the dexmedetomidine significantly reduced mean arterial pressure and heart rate at 30 minutes, blood loss and fentanyl usage.…”
Section: Summary Of Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, it comes in agreement with the previous meta-analyses that showed the beneficial effects of dexmedetomidine in different types of surgeries [35][36][37][38][39][40][49][50][51]. Moreover, a previous meta-analysis conducted by Liu et al [52] evaluating the efficacy and safety of dexmedetomidine in patients who had undergone transsphenoidal surgical resection of pituitary adenoma, including four randomized controlled trials with a total of 160 patients showed that the dexmedetomidine significantly reduced mean arterial pressure and heart rate at 30 minutes, blood loss and fentanyl usage.…”
Section: Summary Of Findingssupporting
confidence: 91%
“…Our study supports the use of dexmedetomidine as an adjuvant anesthesia medication for patients undergoing transsphenoidal resection of pituitary adenoma, which comes in agreement with the previous meta-analyses that recommended the usage of many adjuvant drugs, not only the dexmedetomidine, for anesthesia of different surgeries [ 46 - 48 ]. In addition, it comes in agreement with the previous meta-analyses that showed the beneficial effects of dexmedetomidine in different types of surgeries [ 35 - 40 , 49 - 51 ]. Moreover, a previous meta-analysis conducted by Liu et al [ 52 ] evaluating the efficacy and safety of dexmedetomidine in patients who had undergone transsphenoidal surgical resection of pituitary adenoma, including four randomized controlled trials with a total of 160 patients showed that the dexmedetomidine significantly reduced mean arterial pressure and heart rate at 30 minutes, blood loss and fentanyl usage.…”
Section: Reviewsupporting
confidence: 91%
See 1 more Smart Citation
“…Any language restrictions in the study selection process were not taken into consideration as a constraint for carrying out this evaluation. The complete review includes a PRISMA flow chart 32 that shows the precise status of all identified studies in accordance with the recommendation found in "Part 2, Section 11.2.1 of the Cochrane Guidelines for Systematic Reviews of Interventions". 24 Irrespective of the reporting of outcome data, studies were included in this review as shown in Figure 1.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…https://doi.org/10.6084/m9.figshare.22341559.v1. 32 Data are available under the terms of the Creative Commons Attribution 4.0 International license (CC-BY 4.0).…”
Section: Data Availabilitymentioning
confidence: 99%